2007
DOI: 10.1152/ajpcell.00166.2006
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac fibroblasts influence cardiomyocyte phenotype in vitro

Abstract: Cardiac fibroblasts impact myocardial development and remodeling through intercellular contact with cardiomyocytes, but less is known about noncontact, profibrotic signals whereby fibroblasts alter cardiomyocyte behavior. Fibroblasts and cardiomyocytes were harvested from newborn rat ventricles and separated by serial digestion and gradient centrifugation. Cardiomyocytes were cultured in 1) standard medium, 2) standard medium diluted 1:1 with PBS, or 3) standard medium diluted 1:1 with medium conditioned ≥72 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(128 citation statements)
references
References 51 publications
4
123
1
Order By: Relevance
“…For example, coculture of fibroblasts with myocytes dramatically enhances the expression of cytokines such as IL-6, IL-10, and tumor necrosis factor-␣, compared with cells cultured separately (2,15). These factors in turn alter the structural and contractile properties of the myocytes (2,15). Establishment of electrical contact between adjacent fibroblasts and myocytes may be of critical importance in the release of these cytokines and growth factors.…”
Section: Expression Of Kv Channels In Neonatal Rat Cardiac Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, coculture of fibroblasts with myocytes dramatically enhances the expression of cytokines such as IL-6, IL-10, and tumor necrosis factor-␣, compared with cells cultured separately (2,15). These factors in turn alter the structural and contractile properties of the myocytes (2,15). Establishment of electrical contact between adjacent fibroblasts and myocytes may be of critical importance in the release of these cytokines and growth factors.…”
Section: Expression Of Kv Channels In Neonatal Rat Cardiac Fibroblastsmentioning
confidence: 99%
“…Although cardiac myocytes make up the bulk of the myocardial volume, the cardiac fibroblast is the most numerous cell type found in the heart and functions in the deposition of the extracellular matrix (2, 3). In addition, fibroblasts can serve as "sentinel cells" that coordinate the myocardial response to chemical and mechanical stimulation through the release of cytokines and growth factors (2,3,15). Release of these signals during myocardial injury may regulate the extent of cardiac hypertrophy and fibrosis during the healing process (5, 15).…”
mentioning
confidence: 99%
“…Both IL-10 and VEGF have been reported to have a role in the development of ACS and in subsequent health outcomes [4,5]. In vitro data support the role of these proteins in influencing cardio-myocyte phenotype [6]. Furthermore, our previous data have demonstrated that both IL-6 and MCP-1 are useful for risk stratification for HF/death [2].…”
Section: Discussionmentioning
confidence: 79%
“…However, more specific and earlier mediators of the inflammatory process (e.g., IL-6, MCP-1) may provide better or additional independent information [2]. In addition to IL-6 and MCP-1 there are other cytokines that may be measured that reflect or are indices of inflammation, cardiac fibrosis and cardiomyocyte function that have not been evaluated in this context (e.g., IL-10, VEGF, EGF) [3][4][5][6]. For the present study the objective was to test the hypothesis that a combination of these biomarkers (i.e., IL-6, MCP-1, IL-10, VEGF, and EGF as a panel test) could be used to identify those at high risk for future HF/death.…”
Section: Introductionmentioning
confidence: 99%
“…CCL2/MCP-1) and CXC chemokines (e.g. CXCL1/GRO/KC and CXCL8/IL-8,) in a feed-forward loop driven by the inflammatory milieu, thereby exacerbating the initial inflammatory response (Turner et al, 2007;Turner et al, 2011;Demyanets et al, 2013;LaFramboise et al, 2007). Although further studies are required to determine the precise relative contribution of CF in this early inflammatory stage of remodelling compared with other cell types (mast cells, neutrophils, monocyte/macrophages etc), the available evidence to date suggests that CF play an important role .…”
Section: Inflammatory Phasementioning
confidence: 99%